Pharmacology of cortical epileptic afterdischarges in rats - Kubova, H; Lanstiakova, M; Mockova, M; Mares, P; Vorlicek, J (Epilepsia, 1996)
Afterdischarges (ADs) elicited by electrical stimulation of the sensorimotor cortical area are characterized by rhythmic spikes and spike-wave complexes in the EEG and by clonic face and forelimb seizures. We studied the sensitivity of such ADs to phenytoin (PHT), carbamazepine (CBZ), phenobarbital (PB), primidone (PRM), and valproate (VPA) in 78 adult male Wistar rats with implanted electrodes. Neither PHT (30 and 60 mg/kg intraperitoneally, i.p.) nor CBZ (25 and 50 mg/kg i.p.) suppressed cortical ADs. Indeed, ADs were prolonged by higher doses of both drugs. PRM had a similar effect: A dose of 40 mg/kg transiently shortened ADs, but a dose of 80 mg/kg prolonged ADs. PB (20 and 40 mg/kg) and VPA (200 and 400 mg/kg) were effective in suppressing ADs. Higher doses of VPA and PB reduced the intensity of motor phenomena related to the stimuli but had no effect on the motor correlates of ADs. These findings suggest that cortically induced ADs are not a good model of secondarily generalized seizures. The response to VPA and PB suggests that cortical ADs may represent a model of myoclonic seizures.
Keywords: Dose-Response Relationship, Drug; fenytoin; Rats; vztah mezi dávkou a účinkem léčiva; Electroencephalography; stupeň závažnosti nemoci; Epilepsy; epilepsie; karbamazepin; Phenytoin; epilepsie myoklonické; Disease Models, Animal; antikonvulziva; Rats, Wistar; mužské pohlaví; elektroencefalografie; Valproic Acid; krysa rodu Rattus; Dimethyl Sulfoxide; modely nemocí na zvířatech; mozková kůra; dimethylsulfoxid; zvířata; Anticonvulsants; Cerebral Cortex; Carbamazepine; kyselina valproová; Epilepsies, Myoclonic; potkani Wistar; fenobarbital; Phenobarbital; Severity of Illness Index; Male; Animals